An actantial analysis of selected narratives of participatory development communication in community-based natural resource management - Carpio-Serrano, Lynette B. (2013)
This article is part of a research on the unfolding narratives of participatory development communication (PDC) in an online discussion group of the Adaptive Learning and Linkages in Community-Based Natural Resources Management (ALL in CBNRM) program, an adaptive learning network and a collaborative learning program on participatory development approaches for CBNRM researchers and practitioners in Southeast Asia. This paper explores the use of Greimassian Semio-Narrative Theory and actantial analysis in making sense of the participants' online narratives and interpret the meanings that emerged from their forum about participatory communication in CBNRM.
Keywords: Communication; Community organization